EDUCATION ABOUT TRADITIONAL ELEMENTS IN CURE PATHOLOGICAL WHITENESS - Sri Wulan; Eva Graciella Sihaloho; Fauziah Fitri; Miza Fazlina Ray (JURNAL PENGMAS KESTRA (JPK), 2022)
Pathological vaginal discharge is a type of disease that can attack the female reproductive organs. This abnormal vaginal discharge if not treated immediately can have a fatal effect, for example, it can cause cancer such as cervical cancer or others. There are many ways that can be done to treat pathological vaginal discharge either medically or traditionally, for example by using plants such as betel leaf. Based on the results of previous studies, betel leaf has a lot of content and benefits, including one of them can overcome vaginal discharge, betel leaf is easy to obtain and can be planted in home gardens. traditional ingredients of this betel leaf. The purpose of this community service is to increase adolescent knowledge, especially about pathological vaginal discharge. This community service activity was carried out in Sidodadi Village, Beringin District, with 42 participants, to see knowledge before and after being given education as measured by questionnaires, then the data were analyzed. From the results of the community service, it was found that the characteristics of the majority of respondents aged 16-17 years were 64.3%, 83.3% high school educated and 90.4% unmarried, while the majority of respondents' knowledge before being given education was less than 50% and after education the majority was good as much as 47 ,6%. It is recommended for teenagers to be able to continue to add information about health, especially about vaginal discharge.